THE EFFECTIVENESS OF OPEN BOOK ASSIGNMENTS IN ENHANCING PHARMACOLOGY LEARNING AMONG 3RD YEAR MBBS STUDENTS: A COMPREHENSIVE STUDY. : JPUMHS;2024:14:04,166 170. http://doi.org/10.46536/jpumhs/2024/14.04.575 - Kashif Rasheed Shaikh1 Syed Azhar Hussain Zaid2, Muhammad Abid3, Shuja Anwar Kazi4, Samreen Ali5, Palwasha Abbasi6, Muhammad Atif Ata7, Umair Ali Soomro8 Mehwish Jaweed9 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Pharmacology, a basic subject in the clinical educational program, gives clinical understudies the primary information expected to grasp drug components, remedial mediations, and the clinical use of pharmacology. Traditional assessment strategies in pharmacology frequently center on remembrance, which might restrict further comprehension. Open-book assessments OBAs have arisen as an educational instrument to upgrade decisive reasoning and perception. This study investigates the adequacy of OBAs in working on pharmacological information, decisive reasoning, and clinical application among third-year MBBS Students. OBJECTIVES: This study expects to survey the effect of open book tasks on pharmacology learning results in third-year MBBS students, with a specific spotlight on their capacity to orchestrate data, apply pharmacological standards in clinical settings, and work on scholastic execution. METHODS: A cohort of 100 third-year MBBS students at Suleman Roshan Medical College Tando Adam took part in the review from September 2023 to January 2024. Understudies were allotted open-book assignments focusing on clinical pharmacology situations. Pre-and post-assessment tests were directed to assess the improvement in information, while subjective overviews were utilized to survey understudy fulfillment and saw learning results. RESULTS: 86 students finished the surveys. Huge upgrades were seen in the student’s capacity to apply pharmacological standards in clinical situations p < 0.001. Student’s fulfillment with OBAs was high, with 82% of understudies revealing a superior comprehension of pharmacology and better groundwork for clinical practice. CONCLUSION: Open-book assessments offer a creative way to deal with pharmacology training that advances decisive reasoning, upgrades clinical thinking, and adjusts better to certifiable clinical practice. This study proposes that OBAs ought to be coordinated into the pharmacology educational program to supplement conventional learning techniques and support long-term retention.